2008
DOI: 10.3174/ajnr.a0788
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Tract Abnormalities Are Associated with Weakness in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:The association of MR imaging abnormalities with clinical disability in multiple sclerosis (MS) has been disappointing. This association might be improved by imaging specific functional systems in the central nervous system-for example, the motor system in a patient with weakness. Our aim was to assess the relationship between muscle strength in MS and corticospinal tract (CST) abnormalities detected with multimodality MR imaging of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
(37 reference statements)
3
55
0
Order By: Relevance
“…There is additional evidence that lower aerobic fitness levels (VO 2peak ) were associated with less activation in the right inferior and middle frontal gyri (pr=0.46) and increased activation in the anterior cingulate cortex (pr=-.44) during performance of the Paced Visual Serial Addition Task (PVSAT) in 24 persons with relapsing-remitting MS who had minimal disability [35]. Other researchers have reported that muscle strength of the ankle dorsiflexors and hip flexors, assessed using a hand-held dynamometer, has been associated with brain imaging abnormalities along the intracranial corticospinal tract in 47 persons with moderate MS-related disability [36]. One study reported that larger postural sway amplitude (i.e., worse balance) was associated with reduced structural spinal cord integrity (i.e., cerebrospinal-fluidnormalized magnetization-transfer imaging) in 42 persons with MS who had moderate disability (mean EDSS=3.7) [37].…”
Section: Brian Structure and Function And Fitness Outcomesmentioning
confidence: 99%
“…There is additional evidence that lower aerobic fitness levels (VO 2peak ) were associated with less activation in the right inferior and middle frontal gyri (pr=0.46) and increased activation in the anterior cingulate cortex (pr=-.44) during performance of the Paced Visual Serial Addition Task (PVSAT) in 24 persons with relapsing-remitting MS who had minimal disability [35]. Other researchers have reported that muscle strength of the ankle dorsiflexors and hip flexors, assessed using a hand-held dynamometer, has been associated with brain imaging abnormalities along the intracranial corticospinal tract in 47 persons with moderate MS-related disability [36]. One study reported that larger postural sway amplitude (i.e., worse balance) was associated with reduced structural spinal cord integrity (i.e., cerebrospinal-fluidnormalized magnetization-transfer imaging) in 42 persons with MS who had moderate disability (mean EDSS=3.7) [37].…”
Section: Brian Structure and Function And Fitness Outcomesmentioning
confidence: 99%
“…however, previous authors have failed to prove the relation between the spinal cord MR imaging abnormalities on the conventional sequences and the clinical disability 16,18,19 . Advanced MR imaging techniques, such as proton spectroscopy and diffusion tensor imaging, have also been studied with some success when aiming to demonstrate a correlation between the imaging findings and the clinical status 20 . Also, the DTI have demonstrated fractional anisotropy abnormalities in the brain white matter 7,8 and in the spinal cord 11,12 , even in regions with normal signal on T2-weighted images, defining the well-known terms called "normal appearing white matter" and "normal appearing spinal cord".…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious advantages of DTI at 3 T in comparison to lower field strengths, the number of published applications in MS is rather limited so far [86][87][88][89]. The results of studies performed at 3 T are not likely to differ substantially from those obtained at lower field strengths, 3 T DTI might offer a greater perspective of (multiparametric) MRI research involving certain anatomic regions which are more difficult to investigate at lower fields such as gray matter structures [86,87].…”
Section: Quantitative Mri Methodsmentioning
confidence: 99%